Transport law in Hong Kong - Sze, Ping-fat (Kluwer Law International, 2021)
Derived from the renowned multi-volume 'International Encyclopaedia of Laws', this book provides a systematic approach to transport law as applied in Hong Kong. The book describes the main sources of transport law, jurisdiction and courts, state immunity, and the legal role of transport intermediaries, with detailed reference to maritime law, transport by road, transport by air, transport by rail, and inland navigation. A special chapter is devoted to multimodal transport.00Among the elements of transport law considered are the legal status of the vessel; its acquisition, ownership, and registration; vessel liens and mortgages; the position of master and crew; maritime salvage and assistance; marine pollution; collision; and carriage of passengers. Other topics discussed include liability and limitation of liability, charter parties, and transport under bill of lading. Case law, intergovernmental cooperation agreements, and interactions with environmental, tax, and competition law are also covered.